Development method of protecting images with amplitude-modulated screening using ateb-functions - Nazarkevych, М. (Видавництво Львівської політехніки, 2015)
Proposed method of protection can be used for protection of printed documents and it is not expensive. The theory of Ateb-functions, which is && of classic trigonometry, was used as a mathematical apparatus to develop method of rasterization. A rasterization with amplitudemodulated method for offset printing is developed.
Keywords: rasterization; Atheb-functions; protection of printed documents; amplitude modulation